The 2001 economic crisis in Argentina and its repercussions on tourism policy - Schenkel, Erica Natalia (2016)
This study analyzed mainly tourism policy since 2001. In Argentina tourism became state policy in the post-2001 crisis in order to achieve economic recovery. The actors of the political system decided that tourism played a major role in the government agenda. These policy changes have been accompanied by other political and economic changes. This study opens two debates about the connection between the 2001 crisis and the changing model of tourism in Argentina.